Alignment between an ABC classification and results from an optimization approach. Issue 3 (2nd August 2021) - Larsen, Christian
Abstract: The paper analyzes a multi-item inventory system, using independent (R, Q) policies. The aim is to minimize the average stock level while keeping a weighted (across items) fill rate service level at a given target. The paper explores whether the optimal order sizes and the optimal safety factors are aligned with the ABC classification. Our results show that A items should be ordered more frequently followed by B items and C items. Concerning the optimal safety factors, our results depend on the weights applied in the specification of the weighted service level. If all items have equal weight, A items should have the lowest safety factors followed by B and C items. If the weights are the demand rates, the ranking of the safety factors follows the ratios between the demand rate and the unit purchase price, and the higher this ratio is, the higher is the optimal safety factor. However, this ranking is completely aligned with the ABC classification given that the demands are transformed into monetary units.